The Moderating Role of Feedback on the Effect of Goal-Setting Participation on Innovative Work Behaviour - Pramanik, Purwanti Dyah; Leonandri, Dino G.; Maudiarti, Santi; Achmadi, M.; Adriani, Hanni (APMBA (Asia Pacific Management and Business Application), 2022)
Change is something that is bound to happen. Employees in service industries such as hospitality business must have innovative work behavior to help companies grow and thrive in a constantly changing environment. One way to get employee work integrity in the face of change is to set work goals. The involvement of employees in setting work goals is inseparable from the role of superiors to provide feedback. This study aims to describe the relationship between goal-setting participation and employees' innovative work behavior and their relationship with feedback as a moderating variable. The research methodology uses a quantitative descriptive approach, whereas 101 of four-star hotel employees in Belitung Regency and employed convenience sampling. The results revealed that goal-setting variable has a positive and meaningful relationship with the feedback variable. Moreover, the feedback variable has a role both as an independent and a moderator variable in the relationship between goal-setting variable and innovative work behavior. The implications of the research results provide input to hotel business actors the importance of encouraging goal-setting participation and employing the goals as the positive feedback for the employees.